Critical processes in drug release from HPMC controlled release matrices - Pygall, Samuel R. (2009)
This study has investigated the drug release mechanisms from hydroxypropyl methylcellulose (HPMC) hydrophilic matrices. A hypothesis was developed from interpretation of a previous study that drug surface activity has an influence on drug liberation. The validity of the hypothesis was tested by studying the interactions between HPMC and the two non-steroidal anti-inflammatory drugs diclofenac Na and meclofenamate Na, using tensiometry, rheology, NMR, neutron scattering and turbimetry. Meclofenamate Na was found to interact with HPMC, resulting in detectable changes in drug diffusion coefficients and polymer structure in solution. There were increases in HPMC solution solubility and changes in viscoelasticity, which suggested drug solubilisation of the methoxyl-rich regions of the polymer chains. Diclofenac Na did not show evidence of an interaction and exhibited changes consistent with a 'salting out' of the polymer.